Innovation lowfat EBELABON from chicken egg for weight loss diet overweight students - Fitsyal Febriyadin; Anik Lestari; Sapja Anantanyu (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Overweight is the initial cause of degenerative diseases in the future. The purpose of this study was to determine the effect of a low-fat chicken egg-shredded innovation intervention (EBELABON) on changes in the body weight of overweight students at the Faculty of Health Sciences UMS Surakarta on weight loss. Pre-post group sampling using an experimental research approach. For 14 days, 37 FIK UMS students who met the restriction criteria were included as research participants. They were fed low-fat shredded chicken eggs (EBELABON) twice a day, in the morning (06.00-09.00) and at night (17.00-19.00). Anthropometric measurements using (BIA) and SQ-FFQ were used to obtain data. The results of data analysis using the Paired T-Test showed that the provision of low-fat EBELABON decreased body weight by 2,39 kg, body fat by 2,45%, and nutritional status by 0,94, which was significant (p <0,05) along with nutritional consultation, and there was no difference in the average difference between each treatment group and the provision of low-fat BELABON (p>0,05) using the one-way ANOVA test. In conclusion, the consumption of low-fat BELABON has an effect on weight loss, body fat, and nutritional status in overweight students for 14 days.